Perceived nicotine content of reduced nicotine content cigarettes is a correlate of perceived health risks. Issue 4 (22nd July 2017) - Pacek, Lauren R; Joseph McClernon, F; Denlinger-Apte, Rachel L; Mercincavage, Melissa; Strasser, Andrew A; Dermody, Sarah S; Vandrey, Ryan; Smith, Tracy T; Nardone, Natalie; Hatsukami, Dorothy K; Koopmeiners, Joseph S; Kozink, Rachel V; et al.
Abstract : Background: Reducing cigarette nicotine content may reduce smoking. Studies suggest that smokers believe that nicotine plays a role in smoking-related morbidity. This may lead smokers to assume that reduced nicotine means reduced risk, and attenuate potential positive effects on smoking behaviour. Methods: Data came from a multisite randomised trial in which smokers were assigned to use cigarettes varying in nicotine content for 6 weeks. We evaluated associations between perceived and actual nicotine content with perceived health risks using linear regression, and associations between perceived nicotine content and perceived health risks with smoking outcomes using linear and logistic regression. Findings: Perceived—not actual—nicotine content was associated with perceived health risks; compared with those perceiving very low nicotine, individuals who perceived low ( β =0.72, 95% CI 0.26 to 1.17), moderate ( β =1.02, 95% CI 0.51 to 1.53) or high/very high nicotine ( β =1.66, 95% CI 0.87 to 2.44) perceived greater health risks. Nevertheless, individuals perceiving low (OR=0.48, 95% CI 0.32 to 0.71) or moderate nicotine (OR=0.42, 95% CI 0.27 to 0.66) were less likely than those perceiving very low nicotine to report that they would quit within 1 year if only investigational cigarettes were available. Lower perceived risk of developing other cancers and heart disease was also associated with fewer cigarettes/day at week 6. Conclusions: Although the perception of reduced nicotine is associated with a reduction in perceived harm, it may not attenuate the anticipated beneficial effects on smoking behaviour. These findings have implications for potential product standards targeting nicotine and highlight the need to clarify the persistent harms of reduced nicotine combusted tobacco products.